Optimasi Rute Pengangkutan Sampah Kota Yogyakarta Menggunakan Hybrid Genetic Algorithm - Ekky Armandi; Annie Purwani; Utaminingsih Linarti (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
The increasing population in Yogyakarta City has implications for consumption and solid waste production activities. The waste collection process is the most expensive one in municipal waste management. It is necessary to determine the optimal route for municipal waste collection. In this research, we developed a vehicle routing problem (VRP) with a heterogeneous fleet, multiple trips, intermediate facility, and split delivery to approach the Yogyakarta City waste collection problem. We proposed a hybrid genetic algorithm (GA) to solve the VRP. The result of this study shows that developed VRP can be used to solve the Yogyakarta City waste collection problem.